2016
DOI: 10.1002/2015jg003235
|View full text |Cite
|
Sign up to set email alerts
|

Carbon loss and chemical changes from permafrost collapse in the northern Tibetan Plateau

Abstract: Permafrost collapse, known as thermokarst, can alter soil properties and carbon emissions. However, little is known regarding the effects of permafrost collapse in upland landscapes on the biogeochemical processes that affect carbon balance. In this study, we measured soil carbon and physiochemical properties at a large thermokarst feature on a hillslope in the northeastern Tibetan Plateau. We categorized surfaces into three different microrelief patches based on type and extent of collapse (control, drape, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 50 publications
5
43
0
Order By: Relevance
“…At our site, vegetation recovery after thermokarst formation appears to be slower than in Arctic ecosystems. For example, we observed no vegetation recolonization of exposed patches at our study site over 10 years, and at a similar thermo‐erosion feature on the QTP, there was no growth after 20 to 30 years of recovery [ Mu et al, ]. Slow plant recovery has also been observed in central QTP, where vegetation cover showed no increase after 7 years of ecological protection following anthropogenic disturbance [ Cai et al, ].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…At our site, vegetation recovery after thermokarst formation appears to be slower than in Arctic ecosystems. For example, we observed no vegetation recolonization of exposed patches at our study site over 10 years, and at a similar thermo‐erosion feature on the QTP, there was no growth after 20 to 30 years of recovery [ Mu et al, ]. Slow plant recovery has also been observed in central QTP, where vegetation cover showed no increase after 7 years of ecological protection following anthropogenic disturbance [ Cai et al, ].…”
Section: Discussionsupporting
confidence: 64%
“…This, together with the high‐temperature sensitivity of R eco for exposed patches ( Q 10 = 4), suggests that SOC exposed by thermokarst formation in our study area could be substantially more vulnerable to mineralization following thaw than SOC from other permafrost regions [ Jensen et al, ]. However, considerably more empirical and conceptual research concerning relative biodegradability, climatic differences, hydrological changes, and site level variability is needed before coming to firm conclusions about regional patterns of vulnerability of carbon stocks following permafrost degradation [ Mu et al, ; Olefeldt et al, ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have shown that the total potential soil CO 2 emission on the QTP ranges from 737.90–4224.77 g CO 2 m −1 y −1 , and thawing‐induced CO 2 emissions from permafrost soils would increase general soil respiration by at least about one third on average at a temperature of 5°C (Bosch et al, ). A laboratory incubation experiment indicated that the soils from the AL and PL on the QTP had similar CO 2 ‐emitting potentials (Chen et al, ), while another study suggested that control (nonexposed) soils had significantly higher CO 2 production rates than drape (exposed) soils in a permafrost collapse area on the northern QTP (Mu et al, ). Nevertheless, the abundant carbon stock (~29.6 ± 4.2%; Mu et al, ) was lost during the permafrost thaw and collapse processes, potentially from mineralization, leaching, photodegradation, and lateral displacement.…”
Section: Introductionmentioning
confidence: 99%
“…A laboratory incubation experiment indicated that the soils from the AL and PL on the QTP had similar CO 2 ‐emitting potentials (Chen et al, ), while another study suggested that control (nonexposed) soils had significantly higher CO 2 production rates than drape (exposed) soils in a permafrost collapse area on the northern QTP (Mu et al, ). Nevertheless, the abundant carbon stock (~29.6 ± 4.2%; Mu et al, ) was lost during the permafrost thaw and collapse processes, potentially from mineralization, leaching, photodegradation, and lateral displacement. A recent study for three Tibetan rivers (the Yellow, Yangtze, and Yarlung Tsangpo) showed that the mean radiocarbon age of DOM was 511 ± 294 years before present (BP) during high flow period (August to September 2014), suggesting the significant export of preaged permafrost carbon into the Tibetan rivers (Qu et al, ).…”
Section: Introductionmentioning
confidence: 99%